Advertisement Remove all ads

Differentiate Each of the Following from First Principle: E−X - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads

Differentiate each of the following from first principle:

ex

Advertisement Remove all ads

Solution

\[ \frac{d}{dx}\left( f(x) \right) = \lim_{h \to 0} \frac{f\left( x + h \right) - f\left( x \right)}{h}\]
\[\frac{d}{dx}\left( e^x \right) = \lim_{h \to 0} \frac{e^{- (x + h)} - e^{- x}}{h}\]
\[ = \lim_{h \to 0} \frac{e^{- x} e^{- h} - e^{- x}}{h}\]
\[ = \lim_{h \to 0} \frac{e^{- x} \left( e^{- h} - 1 \right)}{h}\]
\[ = - e^{- x} \lim_{h \to 0} \frac{e^{- h} - 1}{- h}\]
\[ = - e^{- x} \left( 1 \right)\]
\[ = - e^{- x}\]

Concept: The Concept of Derivative - Algebra of Derivative of Functions
  Is there an error in this question or solution?

APPEARS IN

RD Sharma Class 11 Mathematics Textbook
Chapter 30 Derivatives
Exercise 30.2 | Q 2.01 | Page 25

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×